Linking voice of customer to product development through quality function deployment (QFD). (1st January 2011) - Sharma, J.R.
In the present scenario of open-door economic policies, industries have to be one-step ahead than the customers' expectations and meeting these customers' expectations requires the expectations be understood. In this paper, authors have attempted to link voice of customer (VoC) to product development process through quality function deployment (QFD) for complete customer satisfaction. The paper discusses the gathering of customers' voice and their development into structured, evaluated and quantified customer requirements through affinity diagram, along with a detailed discussion on the steps involved in illustrative manner. It also attempts to suggest ways and means to improve and innovate the quality of understanding customers' requirements that drives the design and development of product. The outcome of the study is a system that is objective and methodically derived, which aids not only in quality enhancement programmes but in a variety of product development programmes. The methodology has been applied and tested by means of a real case application on a consumer durable.